Powiązania między turystyką a handlem - Gałecki, Ryszard (Wydział Prawa i Administracji UAM, 1980)
Tourism relationships with national economy are evident. They are the most visible ones in relation to commodity turnover. Share of trade and catering business in general tourist expenditures is significant. In consideration of that tourist economy finds itself in a sphere of interests of trade in many countries. Tourist movement presents different demand in comparison with demand of resident population. Tourist demand is also internally differentiated. It causes significant difficulties for determination of its sizes and structure. Concentration is a fundamental separate feature of tourist demand. This phenomenon is a cause of difficulties in the sphere of commerce, and in consequence of commerce prejudice against tourist movement. A unique treating turnover machines on tourist and non-tourist areas is the source of these difficulties. There is then a need for other organizational and legal regulations. They should enable adjustment of all commercial activity features to special tourist demand. In that way a growth of interests of trade by tourist movement would be caused as a source of economic effects improvement, and not only as a source of additional difficulties. Positive socialized trade attitude towards tourism would also restrain speculative tendencies becoming more intense on areas of intensive tourist movement.
Connections Between Tourism and Trade